ADVERSITY QUOTIENT: COMPLEMENTARY INTELLIGENCE IN ESTABLISHING MENTAL ENDURANCE SANTRI IN PESANTREN - Hasan Baharun; Syafiqah Adhimah (Islam Futura, 2019)
Intellegence Quotient (IQ) and Emotional Quotient (EQ) are not considered as dominant factors in determining a person's success. Another factor that determines a person's success or failure is strong ability to the difficulty of life, this ability is called Adversity Quotient (AQ). Pesantren becomes an institution that strives to build the mental endurance of students with Adversity Quotient (AQ).. The research method used is qualitative research by using a case study approach. This research was conducted at Islamic boarding school of Nurul Jadid Paiton Probolinggo. The results of the study shows that there are efforts to build the mental endurance of santri such as of 1) zone transformation 2) time management 3) systemic organization 4) resolving multicultural conflict 5) unlimited creativity.